The intellectual content of the dialogue in the Iraqi TV series Series of three cities tales as a model (Journal of the College of Basic Education, 2022)
Dialogue is one of the important elements in any TV drama work and has many functions and roles within the structure of the artwork due to the large space that it enjoys، so it has great responsibilities and tasks، including the identification of personalities and the temporal and spatial environment and the detection of some events and details as well as the detection of intellectual contents and their delivery to Viewers. Therefore، the research here is concerned with studying these intellectual implications that the dialogue holds in the TV series. The researcher divided this study into four chapters، from which the methodological framework came to include the research problem، which crystallized in the form of the following question:How to use dialogue to reveal the intellectual content in Iraqi TV drama?As well as the importance of the research، its goals and limits، and the most prominent terms contained in it. The second chapter، entitled Theoretical Framework and previous studies، included three topics، the first of which came under the title language and thought. The second is the title of the relationship of dialogue with the elements of the sham language، while the third has been titled the intellectual content of the dialogue in the series. As for the third chapter: Research procedures. It included the approach used in the research، the research sample، society، and research tool، and included the unit of analysis، then the sample analysis. And chapter four findings and conclusions. It included the final results and conclusions. Finally a list of sources and references.